The mechanisms of morphological-motor functioning in male primary school first-to fourth-graders - Lasan, Mirjam (Kinesiologia Slovenica, 2005)
Four morphological and seven motor variables were assessed in a sample of 2,205 male children (divided into four age groups) aged from 7 to 11 years. Boys were first- to fourth-graders of different primary schools from the Primorje-Gorski Kotar Country, Croatia. The aim of the study was to analyse themorphological-motor structures according to age. A factor analysis was performed for each of the four subject groups. The results clearly show that the morphological-motor functioning of the boys changes with age. Developmental processes lead to the formation of the general morphological factor defined as mesoectomorphy and the general mechanism responsible for motor efficiency in the form of the parallel regulation of strength, speed (movement frequency) and endurance. The results we obtained were found to be consistent with the existing relevant models related to the morphological and motor system. Further, the results allow for the creation of a model integrating relevant elements of the existing models in order to define the function of the body as a whole, which represent the basic determinants of kinesiologic education for primary schoolers.
Keywords: dečki; morfološke lastnosti; motorične sposobnosti; osnovna šola; raziskave; razvoj